(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Low birth weight is one of the deleterious outcomes of pregnancy. To identify the factors contributing to LBW is therefore of paramount importance. But a very little attention had been paid to address the riddle. This effort is to candle the light on maternal socioeconomic factors on birth weight. Objective: To delineate the pattern of birth weight of newborn babies delivered in CMH Dhaka and ascertains selected demographic, socio-economic characteristics of the mothers. Methods & Materials: This cross-sectional study was conducted in Combined Military Hospital Dhaka from September to December 2011 on 110 respondents. Data were collected by interview using semi- structured questionnaire. Data were checked, edited, coded, categorized, cleaned and analyzed using software (SPSS version 16) Results: All the mothers were educated. Mothers who passed SSC exam, 35.5% were highest. Lowest education level was primary, 10%. SSC and below educated mother gave birth to 16.75 LBW babies. The average birth weight babies, 94.74% were delivered by HSC and higher educated mothers. All LBW babies were born other than officer’s family. The mean monthly income was Tk 16533. 33% LBW babies born who had family income _< Tk. 10,000, 52.3% higher birth weight babies had family income _> Tk. 20000 but results was not statistically significant (p>.05). Conclusion: All these findings suggest that a substantial evidence of socioeconomic factors like family income, maternal education and social status has an effect on birth weight. Utilizing health care facilities, better training, educating mother, addressing demographic factors, condition can be improved. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 138-142